2009
DOI: 10.1016/j.neuroimage.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Study of neurovascular coupling in humans via simultaneous magnetoencephalography and diffuse optical imaging acquisition

Abstract: By combining diffuse optical imaging (DOI) and magnetoencephalography (MEG) we investigate neurovascular coupling non-invasively in human subjects using median-nerve stimulation. Previous fMRI studies have shown a habituation effect in the hemodynamic blood oxygen level-dependent (BOLD) response for stimulation periods longer than 2 s. With DOI and MEG we can test whether this effect in hemodynamic response can be accounted for by a habituation effect in the neural response. Our experimental results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…Similarly, Seki et al 44 looked at auditory function using a custom built unshielded MEG and fNIRS system. A more comprehensive study using conventional MEG was done by Ou et al 45 Ou et al used a median nerve electrical stimulation task to look at the relationships of the fNIRS and MEG signals under a parametric stimulation task. They examined the relationship of the amplitude of the optically measured oxy-and deoxy-hemoglobin signals with respect to various physiological peaks in the MEG signal.…”
Section: Comparision Of Fnirs Fmri and Meg Signalsmentioning
confidence: 99%
“…Similarly, Seki et al 44 looked at auditory function using a custom built unshielded MEG and fNIRS system. A more comprehensive study using conventional MEG was done by Ou et al 45 Ou et al used a median nerve electrical stimulation task to look at the relationships of the fNIRS and MEG signals under a parametric stimulation task. They examined the relationship of the amplitude of the optically measured oxy-and deoxy-hemoglobin signals with respect to various physiological peaks in the MEG signal.…”
Section: Comparision Of Fnirs Fmri and Meg Signalsmentioning
confidence: 99%
“…For anesthesia-free neural recording, telemetry systems and linear arrays of microelectrodes have been introduced in behaving small animals (Schregardus et al, 2006) and humans (Keller et al, 2009). Electroencephalogram and magnetoencephalogram also provide less-invasive neural measurements and allow concurrent recording with cortical hemodynamics in anesthetized animals (Franceschini et al, 2008) and in conscious humans (Rosengarten and Kaps, 2010;Ou et al, 2009).…”
Section: Why Is Anesthesia Needed?mentioning
confidence: 99%
“…While topographic DOI methods remain in wide use (Cui et al, 2011;Franceschini et al, 2006;Khan et al, 2010;Lindauer et al, 2001;Ou et al, 2009;Sakatani et al, 2007;, the image quality improvements of HD-DOT methods have been established by several research groups Koch et al, 2010;Zeff et al, 2007). Quantitative comparative studies, using both simulated and in vivo data, have demonstrated clear improvements in resolution of the tomography approach (Boas et al, 2004a;Boas et al, 2004b;Boas et al, 2001;Koch et al, 2010;White and Culver, 2010b).…”
Section: Discussionmentioning
confidence: 99%